Theoretical approach on green school environment : a better learning place for children - Ibrahim, Nuraihan; Mohamed Osman, Mariana; Bachok, Syahriah (2012)

(untitled)
Educational facility is one of the important elements in comprehensive development planning process. Therefore, planning of such facility should promote the sustainable development. Based on Williams (2000), the function of development is to improve well-being of people. For example, it helps is raising living standards and improving education, health, and equality of opportunity that are essential components of economic development. A safe, clean, and well-maintained school with a positive psycho-social climate and culture can foster school connectedness, which in turn boosts children’s educational achievement. School planning and development could become another element of the sustainable indicator for better learning environment of the children.